2001
DOI: 10.2307/3454912
|View full text |Cite
|
Sign up to set email alerts
|

Species of the Toxic Pfiesteria Complex, and the Importance of Functional Type in Data Interpretation

Abstract: We describe the two species of the toxic Pfiesteria complex to date (Pfiesteria piscicida and Pfiesteria shumwayae), their complex life cycles, and the characteristics required for inclusion within this complex. These species resemble P. piscicida Steidinger & Burkholder and also have a) strong attraction to fresh fish tissues and excreta, b) toxic activity stimulated by live fish, and c) production of toxin that can cause fish death and disease. Amoeboid stages were verified in 1992-1997 by our laboratory (va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
110
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(114 citation statements)
references
References 0 publications
4
110
0
Order By: Relevance
“…Additional PfTx is being produced (chemical structure being published elsewhere) so that standards can be developed for routine use. In the interim, various fish assays have been used in attempts to detect toxic Pfiesteria strains (5,6,(10)(11)(12)(21)(22)(23)(24)(25). Although some techniques have provided evidence of toxicity to fish (5,10,14,24), researchers using other methods have concluded that Pfiesteria is not toxigenic at the species [P. shumwayae (21,22)] or genus (23,25) levels.…”
Section: Toxicity and Its Detection In The Dinoflagellate Fish Predatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additional PfTx is being produced (chemical structure being published elsewhere) so that standards can be developed for routine use. In the interim, various fish assays have been used in attempts to detect toxic Pfiesteria strains (5,6,(10)(11)(12)(21)(22)(23)(24)(25). Although some techniques have provided evidence of toxicity to fish (5,10,14,24), researchers using other methods have concluded that Pfiesteria is not toxigenic at the species [P. shumwayae (21,22)] or genus (23,25) levels.…”
Section: Toxicity and Its Detection In The Dinoflagellate Fish Predatorsmentioning
confidence: 99%
“…Under conditions conducive to toxicity expression (9)(10)(11), actively toxic (TOX-A) strains, grown with live finfish, are capable of killing fish with toxin involvement at low to moderate cell densities (Ն4 ϫ 10 2 to 10 3 cells per ml, minutes to several hours). Impacts are exacerbated by Pfiesteria physical attack (6,7,12). The same strains separated from live fish for days or longer can sometimes produce sufficient exotoxin to cause death of sensitive larval stages without physical contact (7).…”
Section: Toxicity and Its Detection In The Dinoflagellate Fish Predatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In preparation for the conference an expert peer-review panel was commissioned to review the existing literature and identify research gaps; the summary of their review is published in this monograph (17). During the meeting, primary Pfiesteria researchers presented previously unpublished results; the majority of those presentations are presented as peer-reviewed articles in this monograph (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The discussion portion of the conference focused upon researcheridentified research gaps.…”
mentioning
confidence: 99%